Factors associated with seropositivity of Hepatitis B & C: A case control study at Azad Jammu and Kashmir - Quddus, Muhammad Abdul; Shahzad, Arslan; Munawar, Rukhsana; Kiani, Rizwan Saeed; Mumtaz, Humayun; Tahir, Rabia (Journal of Rawalpindi Medical College, 2023)
OBJECTIVE: To determine the factors associated with seropositivity of hepatitis B and C at Azad Jammu and Kashmir STUDY DESIGN: Case Control study. SETTING AND DURATION: Department of Gastroenterology Sheikh Khalifa Bin Zayed Al Nahyan Hospital/ AK Combined Military Hospital Rawalakot, from 1s tJanuary 2021 to 30th June 2021. METHODOLOGY: This study involved 173 patients suffering from Hepatitis B or C.144 age and gender matched healthy controls was enrolled from within the hospital. Detailed socio-demographic proforma was filled by both the cases and controls which included all the relevant factors. Pearson chi-square test was applied to look for statistically significant difference in factors associated with seropositivity of hepatitis B and C among cases and controls. RESULTS: A totalof 317 participants were included in the study. 144 were healthy controls and 173 were patients suffering from hepatitis B and C. 149 (86.1%) had hepatitis C while 24 (13.9%) had hepatitis B. Mean age of the study participants were 36.95±3.19 years. Marital status, positive family history of hepatitis B and C and history of surgery or dental procedure had statistically significant relationship with seropositivity of Hepatitis B and C (p-value<0.05) CONCLUSION: Individuals who were married or had anybody in family positive for hepatitis B and C were more at risk of having these infections. In this study dental procedures, surgeries and family history of these infections have highest incidence of risk factors associated with HCV & HBV infections